PERANCANGAN AGRO TECHNO PARK DI SUMBERJAYA LAMPUNG BARAT DENGAN TEMA ARSITEKTUR EKOLOGIS - Cici Okta Novalia, - (2022)
Agro Techno Park di Sumberjaya adalah pusat pengembangan dari hasil perkebunan kopi robusta yang dikelola sebagai tempat kegiatan pendidikan, pelatihan, perkantoran, penginapan dan perdagangan. Agro Techno Park juga didirikan sebagai tempat wisata baru yang berkonsep wisata edukasi. Agro Techno Park di Sumberjaya ini didasari kebutuhan di Kabupaten Lampung Barat. Berdasarkan data, produksi kopi Lampung Barat pada tahun 2010 sebanyak 55.582 ton, tahun 2011 sebanyak 24.907 ton, tahun 2012 sebanyak 57.336 ton, tahun 2013 sebanyak 48.099 ton, tahun 2014 sebanyak 42.746 ton dan tahun 2015 sebesar 52.644 ton. Meskipun produksi kopi Robusta yang stabil di Kabupaten Lampung Barat, hal ini tidak didukung dengan fasilitas yang memadai. Di Provinsi Lampung industri kopi hanya ada di Kota Bandar Lampung dengan total 10 industri, sementara di Kabupaten Lampung Barat belum ada industri kopi. Menyikapi fenomena tersebut, pemerintah Lampung Barat mengembangkan sinergi pariwisata dengan pertanian dengan pengembangan Agro Techno Park. Tujuan perancangan Agro Techno Park ini memfasilitasi kegiatan pendidikan, pelatihan, produksi kopi serta menjadi daya tarik wisata dibidang perkebunan kopi Robusta. Metode yang digunakan adalah metode penelitian dan perancangan (Research and Development) dan analisis deskriptif kuantitatif. Agrotechnopark di Sumberjaya ini menggunakan tema Arsitektur Ekologis. Dengan penerapan tema Arsitektur Ekologis akan lebih mudah dalam mewujudkan sebuah lingkungan yang dapat dilestarikan dengan baik sekaligus memberikan kenyamanan bagi penggunanya. Agro Techno Park akan mampu memberikan tempat bagi masyarakat umum untuk lebih mengenal dan memahami teknologi perkebunan, serta memberikan edukasi terhadap masyarakat khususnya pekebun kopi dan para perintis usaha dibidang perkebunan kopi Robusta. Kata kunci: Agro Techno Park, Arsitektur Ekologis, Kopi Robusta Agro Techno Park Design in Sumberjaya, West Lampung with the Ecological Architecture Theme Cici Okta Novalia- 1601311 ABSTRACT Agro Techno Park in Sumberjaya is a center for the development of robusta coffee plantations which is managed as a place for education, training, offices, lodging and trade activities. Agro Techno Park was also established as a new tourist spot with the concept of educational tourism. This Agro Techno Park in Sumberjaya is based on the needs of West Lampung Regency. Based on data, West Lampung coffee production in 2010 was 55,582 tons, in 2011 as many as 24,907 tons, in 2012 as many as 57,336 tons, in 2013 as many as 48,099 tons, in 2014 as many as 42,746 tons and in 2015 amounting to 52,644 tons. Although Robusta coffee production is stable in West Lampung Regency, this is not based on adequate facilities. In Lampung Province the coffee industry is only in Bandar Lampung City with a total of 10 industries, while in West Lampung Regency there is no coffee industry. Responding to this phenomenon, the West Lampung government has developed a synergy between tourism and agriculture with the development of agro-techno parks. The purpose of designing the Agro Tecno Park is to facilitate education, training, coffee production and become a tourist attraction in the field of robusta coffee plantations. The method used is the method of research and and development and quantitative descriptive analysis. This agrotechnopark in Sumberjaya uses the theme of Ecological Architecture. With the application of the Ecological Architecture theme, it will be easier to create an environment that can be well preserved while providing comfort for its users. Agro Techno Park will be able to provide a place for the general public to get to know and understand plantation technology, as well as provide education to the community, especially coffee planters and business pioneers in the field of robusta coffee plantations. Keywords: Agrotechnopark, Ecological Architecture, Coffee Robusta